Application of the Dempster-Shafer Method in Developing a Web-Based Expert System for Diagnosing Dental and Oral Diseases - Yoseph Pius Kurniawan Kelen (ULTIMATICS, 2025)
Abstract— An expert system is a problem-solving system based on incorporating human expertise into computational models that emulate the analytical approach of experts. Expert systems make it easier for individuals to solve complex problems, even without direct consultation with domain experts. This study aims to develop an expert system that diagnoses dental and oral diseases using the Dempster-Shafer method, which calculates probable diagnoses based on the most prevalent symptoms experienced. The implementation utilizes a web-based framework with PHP and a MySQL database. The expected outcomes include efficient consultations and accurate diagnostic results, providing suitable treatments based on the Dempster-Shafer algorithm.. Index Terms— Expert System; Dempster-Shafer; Dental Disease; Oral Disease